Perjanjian Implementasi (Implementing Agreement) Bab XI Konvensi Hukum Laut 1982 - Etty R Agoes (Fakultas Hukum Universitas Islam Indonesia, 2000)
As a result of lengthy negotiations, the 1982 United Nations Convention on the Law of the Sea, was geared toward the fulfilment for a need of a new dimension in the regulation of the international community's uses of the oceans. However as the new law of the sea is a result of a